Research of Green Supply Chain Supernetwork Model Based on Variational Inequalities - Zhiping Wang; Haichao Wang; Yutang Zou; Jiangning Wu (2009 International Conference on Management and Service Science, 2009)
A green supply chain return supernetwork optimization model is established for a three-tiered supply chain network where m manufacturers are at the upper level and O markets are at the lower level. A supply chain equilibrium model is considered at lower level while the impact and pollution which were caused by cargo freight, cargo package and cargo processing are taken into account at the upper level, the optimality conditions for the manufacturers, distributors and the consumers are established respectively by using the variational inequalities. An example is illustrated to validate the utility of the supply chain supernetwork model in the last part.